2016
DOI: 10.6061/clinics/2016(06)03
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgery for patients with Behcet's disease causing aortic pseudoaneurysm: a shift from open surgery to endovascular repair

Abstract: OBJECTIVES:Behcet’s disease is a form of systematic vasculitis that affects vessels of various sizes. Aortic pseudoaneurysm is one of the most important causes of death among patients with Behcet’s disease due to its high risk of rupture and associated mortality. Our study aimed to investigate the outcomes of Behcet’s disease patients with aortic pseudoaneurysms undergoing open surgery and endovascular aortic repair.METHODS:From January 2003 to September 2014, ten consecutive patients undergoing surgery for ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
1
18
0
2
Order By: Relevance
“…Its advantages are lesser operating time and blood loss, shorter hospital stay, and avoidance of late complications such as recurrence and anastomotic disruption. The literature reports that the success rate of endovascular treatment ranges from 80% to 90%, although there is no clinical evidence suggesting that the endovascular option results in better prognosis for patients with BD with pseudoaneurysms [16,17]. Nevertheless, the endovascular approach was not the best choice in this case because the ruptured false aneurysm involved the visceral segment of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 91%
“…Its advantages are lesser operating time and blood loss, shorter hospital stay, and avoidance of late complications such as recurrence and anastomotic disruption. The literature reports that the success rate of endovascular treatment ranges from 80% to 90%, although there is no clinical evidence suggesting that the endovascular option results in better prognosis for patients with BD with pseudoaneurysms [16,17]. Nevertheless, the endovascular approach was not the best choice in this case because the ruptured false aneurysm involved the visceral segment of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 91%
“…We found six previously reported cases of a recurrent pseudoaneurysm at the proximal margin of an infrarenal stent graft in BD patients. Among them, two patients underwent open surgical repair, 6,7) one patient received careful follow-up observation without additional intervention, 8) and three patients died due to rupture of the pseudoaneurysm. 5,8,9) Although the technique was an off-label use of existing devices, we achieved good results with endovascular repair using the chimney technique in the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair is the standard treatment for aneurysms with dilatation, stenosis, or obstruction, while alternative treatments involve minimally invasive endovascular therapy for aneurysm repair [22, 24, 25]. Shen et al reported that both open surgery and endovascular repair were safe and effective for treating aortic pseudoaneurysm in BD [26]. Furthermore, Naganuma et al reported that ulcer lesions in the ileum and colon, which could lead to intestinal obstruction, were found in surgical patients with intestinal BD [27].…”
Section: Discussionmentioning
confidence: 99%